A new feather mite of the genus Trouessartia Canestrini, 1899 (Acariformes: Trouessartiidae) from the bran-colored flycatcher, Myiophobus fasciatus (Muller PLS, 1776) (Passeriformes: Tyrannidae), in Brazil. Issue 4 (4th July 2022) - Hernandes, Fabio Akashi; Barbosa, Beatriz Bacelar; Ubaid, Flávio Kulaif
ABSTRACT: A new feather mite species of the genus Trouessartia Canestrini, 1899 (Analgoidea: Trouessartiidae) is described from Myiophobus fasciatus (Statius Muller, 1776) (Passeriformes: Tyrannidae) in Brazil. Trouessartia apodemata sp. nov . differs from previously described species of the genus by the unique arrangement of epimerites around the genital apparatus in males, with the lateral tips of the epiandrum fused with epimerites IIIa anterior to the genital apparatus and epimerites IVa fused at their inner tips into a large arch posterior to it. http://www.zoobank.org/urn:lsid:zoobank.org:pub:A0B4C7DA-5E13-4487-8D4C-CA976FEFCB59 http://www.zoobank.org/urn:lsid:zoobank.org:act:32143DF9-A583-4472-B0F9-06AD2C306441